Guardian angel - Muchamore, Robert (London : Hodder Children's Book, 2012)
While undercover, Ryan, an agent for a secret organization of child spies who has saved Ethan's life multiple times, wonders if he can destroy Ethan's family-run criminal empire without hurting Ethan.
Originally published in Great Britain in 2012.
Keywords: Great Britain. -- MI5 -- Juvenile fiction; Great Britain. -- MI5.; CHERUB (Imaginary organization) -- Juvenile fiction; Teenagers -- Great Britain -- Juvenile fiction; Intelligence service -- Great Britain -- Juvenile fiction; Teenagers -- Juvenile fiction; Spy stories; CHERUB (Imaginary organization) -- Fiction; Teenagers -- Fiction; Spies -- Fiction; Intelligence service; Spy stories; Teenagers; Great Britain; Young adult fiction; Series; Fiction; Juvenile works; Spy fiction; Young adult works; Spy stories; Spy fiction